IoT-Based Vaname Shrimp Pond Water Quality Monitoring Using the Quamonitor Tool - syafirah, Marwana; Eso, Rosliana; Husein (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Pond water pollution is the main problem in vannamei shrimp cultivation, so to overcome this problem, The decline in water quality is caused by a decline in the quality of pH, salinity and temperature in pond water. Researchers created the Quamonitor tool to monitor IoT-based vaname shrimp pond water. The research was conducted using the Research and Development (R&D) method with the Analyze, Design, Develop, Implement and Evaluate (ADDIE) model, assisted by WiFi, MQTT and Node Red networks to monitor water in order to display monitoring results on Android. This study aims to monitor the condition of vaname shrimp pond water quality in the form of pH, temperature, and salinity parameters using pH E-4052C sensor, DS18B20 temperature sensor, TDS/Conductivity DFRobot V1.0 sensor and NodeMCU ESP32 as a data manager and system controller that runs in real time. The test results of PH sensors, temperature sensors and TDS/conductivity sensors obtained a sensor error percentage of 0.29% for pH parameters, 1.7% for temperature parameters and 0.41% for salinity parameters. Based on the sensor error value, Thingspeak graph display, real time monitor display on Android, it can be said that the manufacture of the Quamonitor tool for IoT-based vaname shrimp pond water quality monitoring is successful and can function well